Evaluation of educational and artistic trends for teachers of art education in terms of professional competencies in Maysan province - م.د عمار جبار حسين وهج ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2019)
The difficulties faced by teachers of Education arts in primary and secondary schools are considered a major impediment to the non-maturation of the goal of education trends for the upbringing of the generation ,therefore, who are in the process of teaching knowledge of education trends and professional specialization. The purpose of assessing trends is to find out their and find solutions to them. The study discussed the evaluation of the of the realty of the education and artistic trends and methods of teaching in the province of Maysan by the teachers to promote them to the professional competencies they studied and what is produced by the realty of modern theories and sciences the goal was as follow: